2023
DOI: 10.1021/acsami.3c01407
|View full text |Cite
|
Sign up to set email alerts
|

Vapor–Liquid–Solid Growth of Site-Controlled Monolayer MoS2 Films Via Pressure-Induc ed Supercritical Phase Nucleation

Abstract: In this study, a novel pressure-induced supercritical phase nucleation method is proposed to synthesize monolayer MoS2 films, which is promoter free and can avoid contamination of films derived from these heterogeneous promoters in most of the existing techniques. The low-crystallinity and size-controlled MoO2(acac)2 particles are recrystallized on the substrate via the pressure-sensitive solvent capacity of supercritical CO2 and these particles are used as growth sites. The size of single-crystal MoS2 on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 52 publications
1
8
0
Order By: Relevance
“…2(b) and (c)), indicating a likely association with the melting point. In conjunction with prior research, it indicates that from the temperature where the second heat absorption occurs up to 820 °C (growth temperature), MoO 2 gradually transitions into a molten state, 22 as expressed by chemical eqn (2). In summary, it is concluded that the melting point of MoO 2 (acac) 2 increases with higher crystallinity, and there exists a positive correlation between crystallinity and σ.…”
Section: Effect Of Supersaturation On Moo 2 (Acac) 2 Crystallinity An...supporting
confidence: 55%
See 3 more Smart Citations
“…2(b) and (c)), indicating a likely association with the melting point. In conjunction with prior research, it indicates that from the temperature where the second heat absorption occurs up to 820 °C (growth temperature), MoO 2 gradually transitions into a molten state, 22 as expressed by chemical eqn (2). In summary, it is concluded that the melting point of MoO 2 (acac) 2 increases with higher crystallinity, and there exists a positive correlation between crystallinity and σ.…”
Section: Effect Of Supersaturation On Moo 2 (Acac) 2 Crystallinity An...supporting
confidence: 55%
“…Furthermore, according to crystal growth kinetics, the step advancement rate decreases with the increase in step height. 22 Hence, from our experimental results, it is observed that the lateral size of multilayers is smaller than that of single layers. Considering the crystal size and quality, σ is selected as 19, with 1 g sulfur powder as a controlled variable for subsequent investigation.…”
Section: Influence Of Sulfuration Parameters On the Growth Process An...mentioning
confidence: 55%
See 2 more Smart Citations
“…51 At a certain temperature and the same hydrophilicity, the maximum area of the molten particles migrating on the surface is limited. 52 At a low Mo : W ratio, the droplet size is large and the MoS 2 is encapsulated in the droplet. The presence of dangling bonds at the edges of MoS 2 serves as a nucleation site and ultimately forms a lateral heterostructure.…”
Section: Resultsmentioning
confidence: 99%